Pengaruh Penggunaan Media Film Animasi terhadap Keterampilan Menulis Cerpen di Kelas VII SMPN 2 Dlanggu - Jayanti, Rani; Wardani, Dania Kusuma; Ningrum, Seftia Wulan Ayu; Verawati, Amelia Amanda; Hidayat, Taufiq; Azis, Mukhammad Aqmal (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Abstract